The necessity of implementing AI for enhancing safety in the Indonesian passenger shipping fleet - Rahadi, Shinta J.A.; Prasetyo, Dimas Fajar; Hakim, Muhammad Luqman; Sari, Dian Purnama; Virliani, Putri; Rahadi, Cakra W.K.; Rina, Rina; Yulfani, R. D.; Mohammad, Luthfansyah; Kurnianingtyas, Diva (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2024)
The shipping industry, grappling with escalating challenges, increasingly adopts Artificial Intelligence (AI) to enhance efficiency, safety, and environmental impact. Experts endorse ship automation and AI implementation for safety, navigation, and operational efficiency in ferry networks. This paper underscores AIS technology's role in maritime safety and environmental protection, emphasizing AI's potential in navigation and knowledge gap bridging. Indonesia, with its numerous islands and significant population, faces complex challenges in ensuring safe maritime transportation. Collaborative efforts among the government, industry, and stakeholders are vital for enhancing safety standards across the archipelago. Despite regulations, Indonesia contends with a high ferry accident rate, prompting the need for preventive measures. The study reviews AI's application in preventing sea accidents, recognizing its contributions and potential effectiveness in maritime safety. Acknowledging challenges like data quality and cybersecurity, the paper emphasizes the necessity of AI development for passenger ship safety. It concludes by highlighting significant research efforts, endorsing AI's promising role in reshaping the industry for improved efficiency and safety. Further exploration of AI applications, particularly in passenger ship safety, is recommended to meet evolving challenges in the maritime sector.